Danicamtiv reduces myosin’s working stroke but activates the thin filament by accelerating actomyosin attachment - Brent Scott; Lina Greenberg; Caterina Squarci; Kenneth S. Campbell; Michael J. Greenberg (Proceedings of the National Academy of Sciences, 2025)
Heart failure is a leading cause of death worldwide, and even with current treatments, the 5-y transplant-free survival rate is only ~50 to 70%. As such, there is a need to develop new treatments for patients that improve survival and quality of life. Recently, there have been efforts to develop small molecules for heart failure that directly target components of the sarcomere, including cardiac myosin. Danicamtiv is one of these molecules; however, its direct effects on myosin’s single molecule mechanics and kinetics are not well understood. Using optical trapping techniques, stopped flow transient kinetics, and in vitro reconstitution assays, we found that danicamtiv reduces the size of cardiac myosin’s working stroke without affecting actomyosin detachment kinetics at the level of individual crossbridges. We demonstrate that danicamtiv accelerates actomyosin association kinetics, leading to increased recruitment of myosin crossbridges and subsequent thin filament activation at physiologically relevant calcium concentrations. We demonstrate important mechanistic differences with another cardiac myosin binding myotrope, omecamtiv mecarbil. Finally, we computationally model how the observed changes in mechanics and kinetics at the level of single crossbridges can contribute to increased cardiac contraction. Taken together, our results have important implications for the design of sarcomeric-targeting compounds for heart failure.